Mycobacterial Growth Inhibition Assay (MGIA) as a Host Directed Diagnostic Tool for the Evaluation of the Immune Response in Subjects Living With Type 2 Diabetes Mellitus - Bobadilla-del-Valle, Miriam; Leal-Vega, Francisco; Torres-Gonzalez, Pedro; Ordaz-Vazquez, Anabel; Garcia-Garcia, Maria de Lourdes; Tovar-Vargas, Ma. de los Angeles; Delgado-Sanchez, Guadalupe; Guerra De Blas, Paola Del Carmen; Wallis, Robert S.; Ponce-De-León, Alfredo; Sifuentes-Osornio, José (Frontiers in Cellular and Infection Microbiology, 2021)
The lack of efficient and cost-effective diagnostic tools contributes to poor control of tuberculosis in endemic countries. Moreover, host biological processes influence susceptibility, and infection resolution. It is well known that comorbidities such as type 2 diabetes mellitus (DM2) affect the host immune response, making individuals more susceptible to Mycobacterium tuberculosis infection. Currently, there are no laboratory tools that can identify those subjects who have a higher risk of developing the disease. In this study, we used a whole blood mycobacterial growth inhibition assay to assess the immune response capacity to inhibit mycobacterial growth between healthy subjects and those living with DM2 with optimal and poor glycemic control. We also measured cytokine levels in the culture supernatant by cytokine bead arrays. We included 89 patients with DM2: 54 patients with optimal control (mean age 56.2 ± 11.75 years) and 35 patients with poor control (mean age 52.05 ± 9.94 years). We also included 44 healthy subjects as controls (mean age 42.12 ± 11.75 years). We compared the ∆log UFC (a value that represents the difference between mycobacterial growth in the control tube versus the subject’s blood) between each group. Our results demonstrate that patients with DM2 had a lower capacity to inhibit M. tuberculosis growth (∆log UFC DM2 subjects 0.9581 (-0.3897 to 2.495) vs ∆log UFC healthy subjects 0.7190 (-0.2678 to 2.098); p=0.013). Comparing subjects living with DM2 (optimal and poor glycemic control) vs healthy subjects, we found only significant differences between healthy subjects and patients poorly controlled (∆log UFC optimal control group 0.876 (-0.3897 to 2.495); ∆log UFC poor control group 1.078 (0.068 to 2.33); ∆log UFC healthy subjects 0.7190 (-0.2678 to 2.098); p= 0.022). Therefore, glycemic control assessed by glycosylated hemoglobin values influences the capacity of the host to control the infection. Our results confirm that the whole blood mycobacterial growth inhibition assay has potential utility as an in vitro marker of M. tuberculosis immunological control in vivo in subjects living with DM2. This assay can be used to evaluate the immune response of each individual against M. tuberculosis, allowing clinicians to choose a more specific host-directed therapy.